1994
DOI: 10.1136/gut.35.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori stimulates antral mucosal reactive oxygen metabolite production in vivo.

Abstract: To determine if reactive oxygen metabolites have a pathogenic role in Helicobacter pylon (H pylon) related gastroduodenal disease, this study measured their production in antral mucosal biopsy specimens. Two related chemiluminescence techniques were used comparing H pylon positive (n=105) and negative patients (n=64) with a similar spectrum of macroscopic disease. After chemiluminescence assays, biopsy specimens were graded histologically. Increased luminol dependent chemiluminescence (detecting reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
245
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(259 citation statements)
references
References 27 publications
13
245
0
1
Order By: Relevance
“…Because large amounts of ROS are released by infected PMNs, the results of this study support the hypothesis that Hp and neutrophils collaborate to induce host tissue damage and ulceration (8,10,12,13). Moreover, it has been suggested that tissue damage allows Hp to acquire critical nutrients (63).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Because large amounts of ROS are released by infected PMNs, the results of this study support the hypothesis that Hp and neutrophils collaborate to induce host tissue damage and ulceration (8,10,12,13). Moreover, it has been suggested that tissue damage allows Hp to acquire critical nutrients (63).…”
Section: Discussionsupporting
confidence: 71%
“…At the same time, the results of several studies indicate that Hp can activate neutrophils in vitro (3)(4)(5)(6)(7)(8). Moreover, neutrophil density in vivo correlates directly with the ability of Hp to cause severe disease (9 -11), and the available data suggest that neutrophils and bacteria act in concert to induce gastric ulceration (8,10,12,13).…”
Section: Helicobacter Pylori Disrupts Nadph Oxidase Targeting In Humamentioning
confidence: 78%
See 1 more Smart Citation
“…Antigenic similarities, 33 cross mimicry with Lewis X antigen, 34 and autoimmune reactions 35 are possible mechanisms of uveitis caused by H. pylori. As the nature of H. pylori stimulating reactive oxygen metabolite production in gastric mucosa, 36,37 oxidative stress in the trabecular meshwork by H. pylori can also induce decreased outflow capacity and increased IOP. With regard to potential autoimmune reactions, H. pylori infection induces humoral and cellular immune responses following activation of macrophages and produces proinflammatory cytokines (including a variety of interleukins).…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of ROS in the gastric mucosa have been measured in H. pylori-infected patients (9,10). Exposure of gastric epithelial cells to H. pylori resulted in an inflammatory reaction with production of ROS and nitric oxide (11).…”
mentioning
confidence: 99%